Analysis quality control (QC) on CT scan in RSUZA Banda Aceh an effort to get the best quality in image - R. Safitri; Y. Evi; P. Heru; . Bustami (Syiah Kuala University, 2011)
Quality Control (QC) on the Computerized Tomography scanning (CT scan) have been done to ensure the quality of CT scan image. The best quality will improve diagnostic accuracy and ultimately providing maximum services to the patients. QC monitoring has been conducted on the CT scan in the Rumah Sakit Umum Zainal Abidin (RSUZA) Banda Aceh to monitoring the image and measuring the value of Computed Tomography Dose Index (CTDI). The purpose of this study was to determine was dose received by an object and observe the appearance of a clear image. The research was carried out by using pencil ionization chamber detectors to obtain the doses from CT scans and using the phantom to obtain the appropriate image. The results showed that the thickness of slices can affect the dose received at the time of exposure. In this study found no excessive dose received by an object with a very clear picture display